Herencia de la altura de planta de trigo y de otros caracteres en condiciones de la costa central del Perú - Villanueva Novoa, R.; Sanden Ledesma, G.; Orbegozo Arrese, M.; Ramírez Muñante, R. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2025)
Information on the hereditary control of plant height and other characters was obtained from a ´La Molina 60´ X ´Dwarf wheat´cross. Analysis of population means and frequency distribution for plant height suggests the operation of more than one type of gene action. The results obtained on the inheritance of tillering, weight of kernels per head and heading time suggest the operation of a small number of genes in the expression of such characters. The inheritance of number of kernels per head apparently was governed by polygenic action. The F2 distribution was the only one that approached a normal curve. Probably both major and minor factors controlled the expression of rachis length because in the F2 distribution in this character a transgressive segregation occurred. Significant correlations were obtained between the following characters. Number of tillers per plant X rachis length; number of kernels per hand X rachis length and weight of kernels per head X number of kernels per head.